Keterlibatan Ayah dalam Pengasuhan dan Dampaknya pada Aspek Perkembangan Anak (Literatur Review) - Bili, Fransiskus Ghunu; Bili, Dominggus Lero; Bessu, Lidia Vera; Haingu, Rahel Maga (Indo-MathEdu Intellectuals Journal, 2025)
The involvement of fathers in parenting has a positive effect on aspects of child development and provides psychological results from time to time. The purpose of this article is to explore several research literature in the form of journals or scientific articles related to fathers' involvement in parenting and its impact on children's development both in terms of social-emotional, cognitive, language, and moral. The methodology used is a literature review of journal articles that focus on the word father's involvement in parenting and some impacts on aspects of child development which are then analyzed to obtain an explanation of the role of the father's involvement and described descriptively. The results of the analysis describe the definitions of father and parenting, father's involvement in parenting, the function of father's involvement in parenting, its impact on child development, and the model of father's involvement programs. With the involvement of fathers in parenting, aspects of child development develop optimally